The Impact of Urbanization on Public Health in Jakarta Focusing on Air Quality and Respiratory Disorders - Lestari, Maria (Generasi Sains Indonesia, 2024)
This study investigates the impact of rapid urbanization on public health in Jakarta, Indonesia, with a specific focus on air quality and its effects on respiratory disorders. Jakarta, a rapidly growing urban center, faces significant air pollution due to increased vehicular emissions, industrial activities, and population density. This research evaluates air quality data and the prevalence of respiratory diseases, including asthma, bronchitis, and chronic obstructive pulmonary disease (COPD), in both urban and suburban areas of Jakarta. The study uses a quantitative approach, analyzing air pollutant levels (PM2.5, NO2, CO, and O3) and health data over a one-year period, with an emphasis on demographic factors such as age, gender, and socio-economic status. The results reveal that urban areas experience significantly higher pollutant levels compared to suburban areas, leading to a higher prevalence of respiratory disorders. Furthermore, seasonal variations, with worsened air quality during the dry season, exacerbate the health impacts, particularly among vulnerable populations such as children, the elderly, and low-income groups. The study highlights the urgent need for effective urban air quality management, public health interventions, and policies to mitigate the adverse effects of pollution on respiratory health. The findings emphasize the importance of addressing the socio-economic disparities in health outcomes and the need for targeted healthcare solutions in high-pollution urban areas.